Новый вид самотерия из мэотиса Северного Причерноморья - Короткевич, Е.Л. (Вестник зоологии, 1978)
The new species S. maeoticum sp. n. is described from the Meiotic fauna of the Odessa region (Kostev ravine, vil. Novaja Emetovka. Beljaevkian district). It differs from the other species by a bigger skull, elongated brain and relatively narrow and high face parts of the skull, non-coulisses-like arrangement of premolars, their shape and other peculiarities of teeth structure.